The Influence of Food and Beverage Sub-Sector Manufacturing Companies Value on Financial Performance Listed Indonesia Stock Exchange - Hatuwe, Masna; Muspiha; Firman Gazali Djunaidi; Hamiru; Hayati Hehamahua (International Journal of Management Progress, 2023)
This study aims to assess the effect of financial performance on the value of manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange for the 2019-2021 period. The research method used is quantitative analysis with the analytical tool used is multiple linear regression. This research was conducted at food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange by accessing the official website of the Indonesia Stock Exchange, namely www.idx.co.id. The results showed that partially profitability had a negative and insignificant effect on firm value, leverage had a negative and insignificant effect on firm value, liquidity had a positive and insignificant effect on firm value, while activity had a positive and significant effect on firm value. Simultaneously profitability, leverage, liquidity and activity simultaneously have a significant effect on the value of manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange.